Enhancing recovery in older patients undergoing abdominal surgery: Examining the effect of a preoperative preparation program using a quasi-experimental design - Issarapong Penphumphuang; Yaowarat Matchim; Prasit Mahawongkhajit; Thanyarat Boontoi (Belitung Raya Foundation, Indonesia, 2023)
Background: Older adult patients often experience delayed postoperative recovery due to a lack of self-efficacy in engaging in physical activities during early rehabilitation. Concurrently, family caregivers play a crucial role in caring for older adults. However, the extent of family involvement in improving self-efficacy and facilitating recovery following major abdominal surgeries in older adults remains largely unexplored. Objective: This study aimed to examine the effect of a preoperative preparation program on the recovery of older patients undergoing major abdominal surgeries. Methods: A quasi-experimental study with a two-group, pretest-posttest design was conducted. The participants included 60 older adult patients undergoing abdominal surgeries at Thammasat University Hospital, Thailand, between September 2019 and March 2020. Participants were selected by purposive sampling with the inclusion criteria and were assigned to the experimental (n = 30) or the control (n = 30) groups using matched pair according to the type of operation. The control group received standard care, while the intervention group underwent a two-week preoperative preparation program developed based on self-efficacy theory and family support. Data were collected using validated tools. Recovery was assessed at one week and two weeks after surgery. Descriptive statistics, as well as dependent and independent t-tests, were used for data analysis. Results: The results revealed that the intervention group had significantly higher mean recovery scores than the control group at one week (M = 56.93, SD = 16.42; M = 44.60, SD = 16.30, t = -2.92, df = 58, p <0.01) and two weeks after surgery (M = 66.64, SD = 8.63; M = 61.68, SD = 7.86, t= -2.33, df = 58, p <0.05) when comparing between the two groups. Conclusion: The preoperative preparation program effectively enhanced recovery one week and two weeks after surgery. The study findings can be valuable for nurses in implementing the preoperative preparation program to facilitate recovery among older adult patients undergoing abdominal surgeries.